Retroperitoneal fibromatosis presenting as a mesenteric mass: A case report. Issue 17 (April 2020) - Xiao, Jianchun; Zhou, Wenzhe
Abstract: Rationale: Fibromatoses or desmoid tumors are relatively rare tumors derived from the musculoaponeurotic system. This tumor has no specific clinical symptoms and it is sometimes misdiagnosed as other diseases such as gastrointestinal stromal tumors (GISTs). Patient concerns: A 28-year-old man visited Peking Union Medical College for a tangible abdominal mass without abdominal pain or distention. Diagnoses: Considering the imaging characteristics and clinical manifestation, this mass was primarily diagnosed as GIST before surgery. During the surgery, the occupancy was found under the ileocecal mesentery, with grayish white appearance, tough texture, and poor mobility, which was not consistent with the character of the GIST. After the surgery, pathological examination and individual immunohistochemistry results demonstrated that the lesion was compatible with the diagnosis of retroperitoneal fibromatosis with purulent inflammation of chronic lymphadenitis. Interventions: Therefore, we decided to perform tumor mass resection, right colon resection, partial duodenum resection, and intestinal anastomosis on laparotomy, but the right ureter was retained. After excision of the tumor, the ends of the intestine segment were continuously sutured. Outcomes: The patient experienced no intraoperative or postoperative complications, and was discharged 3 days after surgery. Periodic follow-up physical examinations such as the abdominal ultrasound and computed tomography were performed each 3 months, and no evidence of recurrence was observed during the whole 12 months. Lessons: To sum up, intra-abdominal fibromatosis is an extremely rare tumor that must be differentiated from other tumors of the digestive tract, and pathological and immunohistochemical examination is a critical part of the diagnosis. Early diagnosis of fibromatosis is essential for the outcome. Extensive resection of the mass minimizes the risk of relapse.